Study of Ultrasound in Acute Abdomen at Ccmmc and Hospital, Durg - Shah, Dr. Urvil A.; Shah, Dr. Anil K. (International Journal of Innovative Research in Medical Science, 2018)
Acute abdomen is a term frequently used to describe the patients who are having abdominal tenderness and rigidity. Before the use of imaging technique, these patients were candidates for surgery. Ultrasound plays an important role in the initial evaluation of the acute abdomen. Ultrasound may be used as a first line of investigation in order to make a definitive diagnosis or can be used as a triage tool to direct subsequent patient management appropriately. Ultrasonography remains the primary imaging technique in the majority of cases, especially in young and female patients, when there is a limitation of the radiation exposure. Material and methods: 50 cases of acute abdomen were selected for the study. Patients with trauma and with compromised vital signs were excluded from the study. History taking and thorough clinical examination was carried out. All necessary biochemical and haematological investigations were carried out. Provisional diagnosis was made on the basis of sonographic findings. Results: 27 patients were male and 23 were females. Mean age of the patients was 36.34± 21.03 years. Final diagnosis was made on the basis of operative procedure, histopathology and therapeutics. Finally, 15 (30%) cases were diagnosed as acute appendicitis. 9 (18%) were diagnosed as acute cholecystitis, 4 (8%) each as pancreatitis, ulcer perforation and instentinal obstruction, 2(4%) each were diagnosed as ectopic pregnancy, Amoebic liver abscess, psoas abscess and Renal cause, 4 (8%) were diagnosed as pelvic inflammatory disease and 2 (4%) were chronic liver disease. Among the surgically treated patients, 38 patients (72%) were correctly diagnosed by preoperative ultrasonography. These included acute appendicitis (n = 14), acute cholecystitis (n = 10), ulcer perforation (n = 4), and liver abscess (n = 2), ectopic pregnancy (n=2), intestinal obstruction (n=4) and psoas abscess (n= 2). Conclusion: Ultrasonography plays an important role in the evaluation of the acute abdomen and initial evaluation by supporting the differential diagnosis.